1999
DOI: 10.1046/j.1365-2249.1999.00885.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacilli from human gastrointestinal mucosa are strong stimulators of IL-12 production

Abstract: SUMMARYInteraction of macrophages with bacteria is a stimulus for production of cytokines such as IL-10 and IL-12. IL-12 stimulates T cell and natural killer (NK) cell cytotoxicity and interferon-gamma (IFN-g) production. IL-10 opposes the T cell-stimulating action of IL-12, decreases the release of proinflammatory cytokines from macrophages, and stimulates B cells. We have studied the capacity of human intestinal isolates from the three Lactobacillus species dominating on the human gastrointestinal mucosa, L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
145
2
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(170 citation statements)
references
References 38 publications
15
145
2
6
Order By: Relevance
“…Indeed we, and others, showed that probiotics present distinct strainspecific immunomodulatory capacities in vitro (Hessle et al, 1999;Maassen et al, 2000;Mercenier et al, 2004) which can be closely correlated with their in vivo anti-inflammatory potential. Interestingly, the anti-inflammatory effects of lactobacilli observed after either oral or systemic administration (Foligne et al, 2005;Sheil et al, 2004), suggest that the protective mechanisms might involve regulatory-cell populations.…”
Section: Iii2b : Functional Food: Conceptsupporting
confidence: 54%
“…Indeed we, and others, showed that probiotics present distinct strainspecific immunomodulatory capacities in vitro (Hessle et al, 1999;Maassen et al, 2000;Mercenier et al, 2004) which can be closely correlated with their in vivo anti-inflammatory potential. Interestingly, the anti-inflammatory effects of lactobacilli observed after either oral or systemic administration (Foligne et al, 2005;Sheil et al, 2004), suggest that the protective mechanisms might involve regulatory-cell populations.…”
Section: Iii2b : Functional Food: Conceptsupporting
confidence: 54%
“…While we can provide no further evidence here as to the molecular signalling mechanisms by which B. lactis is able to enhance cellular immunity, it is known that phagocytic cells are stimulated by direct contact with LAB and sub-cellular fractions of bacterial cell walls (Keller et al, 1994;Miettinen et al, 1996). Furthermore, recent studies have indicated that LAB also induce mononuclear leucocytes to secrete procellular immunity cytokines such as interleukin-12 and interleukin-18, both of which are potent stimulators of NK cell activity and interferon production (Miettenen et al, 1999;Hessle et al, 1999). It is therefore possible that immune enhancement in humans by dietary consumption of B. lactis is due primarily to stimulation of the inter-communicating cytokine network, which serves to drive the immune system toward a general enhancement of cellular immune function.…”
Section: Discussionmentioning
confidence: 99%
“…Different factors have been reported to contribute to the protective function of gut microflora such as maintaining a physical barrier against colonization or invasion by pathogens, facilitating nutrient digestion and assimilation, and providing immunological surveillance signals at the gut mucosalumen interface (5). It is widely accepted that the intestinal microflora plays an important role in maintaining the health of the host and possesses immunomodulating capacities (6)(7)(8)(9)(10). Lactic acid bacteria (LAB) are normal inhabitants of the human gastrointestinal tract and are major components of the dominant flora in the small bowel.…”
mentioning
confidence: 99%
“…We established that the in vivo protective effect of LAB in a murine 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced model of colitis is strain-specific (20,21). Several LAB strains were reported to exert in vitro stimulatory properties on cells of the innate immune system, including macrophages and natural killer cells, and to induce the production of both proinflammatory cytokines, such as TNF-␣ and IL-12, and the antiinflammatory IL-10 cytokine (6,7,10,22). Previous reports have suggested that Gram-positive bacteria tend to preferentially stimulate IL-12 secretion, whereas Gram-negative bacteria predominantly induce IL-10 from stimulated monocytes and macrophages (23).…”
mentioning
confidence: 99%